Freedom of Contract in Choosing a Financial Services Sector Consumer Dispute Resolution Forum - Adelia Kusuma Wardhani; Damar Sugeng Utomo; Indra Marga Wicaksono (Kertha Patrika, 2025)
The choice of dispute resolution forum is a freedom for the parties contained therein. This includes Financial Services Sector Consumers who have the right to choose the forum. However, Law Number 4 of 2023 concerning Strengthening and Development of the Financial Services Sector has shifted this freedom for consumers which is only given to the Financial Sector Alternative Dispute Resolution Institution. This research aims to analyze the freedom of contract for consumers to choose a dispute resolution forum based on the principle of proportionality in an agreement. This research uses normative and doctrinal research. This research is conducted by examining literature or secondary data sourced from primary legal materials, secondary legal materials, and tertiary legal materials. The regulation regarding the dispute resolution forum in Law Number 4 of 2023 concerning Strengthening and Development of the Financial Sector does not in fact provide a freedom of contract for the parties therein. Given that choosing a forum is a basic right for consumers, it is better for business actors to provide all available dispute resolution forums. From the many choices of dispute resolution forums, consumers are given the right to choose a dispute resolution forum before agreements in the financial services sector are approved and electronically signed by consumers.